Workplace violence against doctors and dentists and their opinion during the pandemic - Belingheri, Michael; Riva, Michele Augusto; Perconte, Claudio; Teruzzi, Carlo Maria; Paladino, Maria Emilia (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: HCWs are particularly susceptible to diverse forms of workplace violence (WPV), and the COVID-19 pandemic has significantly altered the landscape of healthcare delivery, potentially influencing the dynamics of violence in healthcare settings. Many studies are about nurses but only few studies investigate WPV among doctors and dentists. This study sought to assess the phenomenon of WPV against doctors and dentists during the pandemic (type, characteristics of the aggressor, the victim, and the setting, subsequent actions) and to evaluate the opinions of the HCWs on the role of the pandemic on the WPV. Methods: An online survey was conducted from February to May 2022 among physicians and dentists registered with any medical board in Lombardy, the Italian region most affected by the pandemic. The survey included questions on demographic information, experiences of WPV in the past 12 months, and views on the pandemic’s impact on WPV. Results: Out of 1,295 respondents, 38.2% reported experiencing WPV, predominantly verbal harassment and threats, mainly from patients and their relatives. Incidents were more frequent on weekdays and in the afternoon. A significant portion of HCWs believed that the COVID-19 pandemic contributed to an increase in WPV. Conclusions: The findings call for the implementation of targeted interventions, including improved communication training, enhanced support and reporting mechanisms, organizational changes to mitigate the risk factors for violence, and personal defense tools.